Clinical manifestations of geriatric depression in a memory clinic: Toward a proposed subtyping of geriatric depression - Dillon, Carol (2011)
BACKGROUND: As the older population increases so does the number of older psychiatric patients. Elderly psychiatric patients manifest certain specific and unique characteristics. Different subtypes of depressive syndromes exist in late-life depression, and many of these are associated with cognitive impairment. MATERIALS AND METHODS: A total of 109 depressive patients and 30 normal subjects matched by age and educational level were evaluated using a neuropsychiatric interview and an extensive neuropsychological battery. Depressive patients were classified into four different groups by SCAN 2.1 (schedules for clinical assessment in Neuropsychiatry): major depression disorder (n: 34), dysthymia disorder (n: 29), subsyndromal depression (n: 28), and depression due to mild dementia of Alzheimer's type (n: 18). RESULTS: We found significant associations (p<.05) between depressive status and demographic or clinical factors that include marital status (OR: 3.4, CI: 1.2-9.6), level of daily activity (OR: 5.3, CI: 2-14), heart disease (OR: 12.5, CI: 1.6-96.3), and high blood cholesterol levels (p:.032). Neuropsychological differences were observed among the four depressive groups and also between depressive patients and controls. Significant differences were observed in daily life activities and caregivers' burden between depressive patients and normal subjects. CONCLUSION: Geriatric depression is associated with heart disease, high cholesterol blood levels, marital status, and daily inactivity. Different subtypes of geriatric depression have particular clinical features, such as cognitive profiles, daily life activities, and caregivers' burden, that can help to differentiate among them. LIMITATIONS: The cohort referred to a memory clinic with memory complaints is a biased sample, and the results cannot be generalized to other non-memory symptomatic cohorts.